Knowledge and Patient Compliance in Root Canal Treatment - Tri Wahono; Silvia Prasetyowati (Alliance oh Health Activists (AloHA), 2019)
One factor of unfinished root canal treatment is a factor of knowledge, motivation and ability about root canal treatment that affects a person compliance to overcome the problems which they experience. There are many patients who are not come to complete their root canal treatment. The purpose of this study is to analyze patient compliance, motivation and ability towards the compliance of root canal treatment. The type of research used was cross sectional. The subjects of this study were all root canal treatment patients who came to dental polyclinics from July to October. In this study data collection methods used were questionnaires and observations. Data analysis were analyzed using Fisher exact test. The results of this study showed that there was no relationship between knowledge, motivation and ability towards the compliance of root canal treatment. Keywords: Root canal treatment, Knowledge, Motivation, Ability, Compliance